Financial inclusion through gold pawn services in Indonesia: A comparative analysis of conventional and Islamic systems - Muhammad Thoha Ainun Najib; Khoirun Nisak; Endah Setyowati (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Financial inclusion is essential for inclusive economic development, particularly in developing countries where access to formal financial services remains limited. In Indonesia, gold pawn services provided by non-bank financial institutions serve as an important alternative financing mechanism for communities facing barriers to banking access. These services operate under conventional and Islamic systems, yet comparative empirical evidence on their roles in promoting financial inclusion remains limited. This study aims to analyze the role of gold pawn services in enhancing financial inclusion in Indonesia, considering operational and macroeconomic factors, and to compare inclusion mechanisms between conventional and Islamic systems. Methods: This study employs a quantitative approach, drawing on secondary data on gold pawn services in Indonesia. Financial inclusion is proxied by the ratio of service outlets to gold pawn accounts, reflecting spatial and institutional accessibility. A stacked regression model is applied to examine the effects of operational factors and economic growth while capturing structural differences between the two systems. Findings: The results show that operational factors significantly influence financial inclusion in both conventional and Islamic gold pawn services. Economic growth also affects financial inclusion, with differing sensitivities observed between the two systems, indicating distinct operational and structural mechanisms. These findings support the theoretical view that alternative financing instruments with simplified access can complement the formal financial system in expanding financial inclusion. Conclusion: Gold pawn services contribute significantly to financial inclusion in Indonesia, with clear differences in the mechanisms of inclusion between conventional and Islamic systems. Novelty/Originality of this article: This study contributes by using the outlet-to-account ratio as a proxy for financial inclusion and by providing an integrated empirical comparison of conventional and Islamic gold pawn services.